Pembuatan Konten Instagram Reels Menggunakan Aplikasi Capcut sebagai Strategi Brand Awareness di Segobong Malang - Deva Januar Azis; Rr. Tri Istining Wardani; Dwi Sudjanarti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Social media has become an effective digital marketing tool for increasing brand awareness. Segobong Malang, a culinary UMKM, has an Instagram account but has not consistently uploaded engaging content, resulting in low brand awareness. This study aims to develop Instagram Reels content using the CapCut application as a brand awareness strategy.This study employed the Action Research method based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, questionnaires, and documentation involving 15 respondents, including one business owner, two design experts, two marketing experts, and ten consumers. Brand awareness was measured using the indicators of brand recall, brand recognition, brand purchase, and brand consumption, while content performance was evaluated using the Key Performance Indicator (KPI) based on the engagement rate. The results indicate that the Instagram Reels created using CapCut improved all brand awareness indicators. Furthermore, the three published reels achieved an engagement rate above 6%, which falls into the excellent category, indicating a high level of audience interaction. Most respondents also reported becoming more familiar with and able to recall the Segobong Malang brand after watching the reels. It can be concluded that well-planned Instagram Reels are effective in increasing the brand awareness of Segobong Malang. Therefore, the UMKM is encouraged to consistently create and manage Instagram content as part of its digital marketing strategy.